Indium Tin Oxide-Free Inverted Organic Photovoltaics Using Laser-Induced Forward Transfer Silver Nanoparticle Embedded Metal Grids - Pozov, Sergey M.; Andritsos, Kostas; Choulis, Stelios A. (My University, 2022)
Laser-induced forward transfer (LIFT) printing has emerged as a valid digital printing technique capable of transferring and printing a wide range of electronic materials. In this paper, we present for the first time LIFT printing as a method to fabricate silver (Ag) nanoparticle (np) grids for the development of indium tin oxide (ITO)-free inverted PM6:Y6 nonfullerene acceptor organic photovoltaics (OPVs). Limitations of the direct use of LIFT-printed Ag np grids in inverted ITO-free OPVs are addressed through a Ag grid embedding process. The embedded laser-printed Ag grid lines have high electrical conductivity, while the Ag metal grid transparency is varied by altering the number of Ag grid lines within the inverted OPVs' ITO-free bottom electrode. Following the presented Ag-grid embedding (EMP) process, metal-grid design optimizations, and device engineering methods incorporating an EMB-nine-line Ag np grid/PH500/AI4083/ZnO bottom electrode, we have demonstrated inverted ITO-free OPVs incorporating laser-printed Ag grids with 11.0% power conversion efficiency.
Keywords: Ag nanoparticle ink; Charge selective contacts; Inverted organic photovoltaics